Diagnostic utility of neutrophil CD64 as a marker of early-onset sepsis in very low birth weight neonates - Meena, Kessh Ram; Tiwari, Priyanka; Debata, Pradeep (Indian Journal of Child Health, 2018)
Background: Sepsis is a major cause of neonatal morbidity and mortality. It is extremely important to make an early diagnosis of sepsis, as early recognition and prompt institution of treatment is critical for improved outcome. Objectives: This prospective observational study was aimed to evaluate the diagnostic utility of neutrophil CD64 expression for the identification of early-onset sepsis in very low birth weight (VLBW) neonates. Methods: All VLBW neonates with signs and symptoms of sepsis before 72 h of age, born to mother with or without risk factors for sepsis were enrolled. Complete blood cells count, C-reactive protein, absolute neutrophil count, I/T ratio, blood culture, and neutrophil CD64 assessment were performed. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of neutrophil CD64 and its combination with other hematological makers for sepsis were measured. Results: A total of 302 VLBW neonates were enrolled; of which, 151 were cases and 151 were controls. Neutrophil CD64 was significantly increased in cases than in controls (p